In memoriamDoctor Pedro G. Aguilar Fernández: November 1926 - October 2013 - Romero, Leonardo (2013)
Dr. Pedro Aguilar Fernández died on October 2, 2013. He was born in Cañete, south of Lima on November 28, 1926. he was our magazine Collaborator of and colleague. recognized in the sphere of Peruvian biological sciences for his participation in several academic and professional activities.